Social Responsibilities of Islamic Religious Education Teachers To The Community of Gayo Lues, Aceh, Indonesia - Masykur Pulo Tukok; Warul Walidin; Anton Widyanto; Silahuddin Silahuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
This study aimed to determine the social responsibility of Islamic Religious Education teachers to the people of Gayo Lues Regency, the community's responses to the social responsibility of Islamic Religious Education teachers of Gayo Lues Regency, and the contribution of Islamic Religious Education Teachers to Knowledge in Gayo Regency Lues. This study was conducted in the form of qualitative field study. Interviews and documentation were employed as data collection techniques. The findings of the study indicate that some PAI teachers engage in forms of social responsibility with an inclusive, objective, nondiscriminatory, adaptable, and communicative attitude that manifests itself in both religious and nonreligious fields. Positive responses were received in the form of support, willingness to participate, and a desire to maintain the role of the PAI teacher in response to the social responsibility undertaken. Negative response where PAI teachers are less involved and participate less in the community, and where PAI teachers are considered to be confined to teaching at school without engaging with the adjacent community. Regarding PAI teachers' contribution to education in Gayo Lues Regency, it is carried out to the greatest extent possible, beginning with the provision of all extant skills to students and the surrounding community. Additionally, PAI teachers constantly teach Duha prayers as sunnah prayers for students.